Functionally Graded Materials (FGM) for Spacers in Gas Insulated Systems: A Concise Review and Some Comments - Wong, K. L.; Danikas, M. (Engineering, Technology & Applied Science Research, 2021)
Functionally Graded Materials (FGMs) present a solution to control electrical stresses in high voltage applications. In this paper, a concise review is presented on the FGMs for spacers in gas-insulated systems. FGMs offer the possibility of a more even electric field distribution and thus a viable solution for industrial applications. FGMs are investigated here primarily as materials for permittivity control. Some aspects of FGMs are discussed as well as some thoughts on future challenges.